Sistem Pakar Diagnosa Awal Penyakit Ginjal Menggunakan Metode Forward Chaining - Rukmawati Rukmawati; Ismail Ismail; Nurhikma Ramadhani (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2026)
The kidneys are a vital organ in the body's metabolic system. Most people still lack understanding of the importance of their role in the human body, especially the various diseases that can arise in the kidney area. They are also less familiar with the symptoms of kidney disease. Kidney disease requires specialist doctors to diagnose it, which is relatively expensive, and the number of nephrologists in Indonesia is still limited. Limited knowledge about kidney disease and the limited number of nephrologists makes it difficult for the public to diagnose kidney disease early. The system development methodology used is the Extreme Programming (XP) methodology. This study builds an expert system application for the early diagnosis of kidney disease using the inference method, namely the forward chaining method. A survey was conducted with 20 respondents selected by sampling to test the design and usability of the application. After conducting UAT (user acceptance task) testing, the average UAT percentage of respondents was 84.4%. This study assessed the design and usability of the kidney disease expert system application.